(untitled) (Theatrum historiae, 2012)
The paper deals with the new facts concernig the sculptures by Matthias Bernard Braun (1684–1738) in Kuks. In addition to a new assessment of the Eight Beatitudes outside the hospital chapel, the article deals with Braun’s relation to the ancient sculpture and the artistic buzz in the Baroque Vienna. These two artistic phenomena influenced the sculptor’s work more than we have thought so far.